Health Literacy and Geography: Examining Environmental and Socioeconomic Influences on Public Health Awareness - Nugrahani , Marshanda Rimadita (Yayasan Sinergi Kawula Muda, 2023)
Health literacy is essential for informed health decision-making, yet disparities persist due to geographical, environmental, and socioeconomic factors. This study systematically reviews existing literature to examine how these variables influence public health awareness. A comprehensive search of PubMed, Scopus, and Google Scholar identified relevant studies published in the last decade. Findings reveal that individuals in rural and low-income communities experience significant barriers to accessing reliable health information due to limited healthcare infrastructure, digital divide, and environmental stressors such as pollution and inadequate sanitation. Furthermore, disparities in formal education and socioeconomic status contribute to the uneven distribution of health literacy levels. Digital health solutions, including mobile health applications and telemedicine, have demonstrated potential in bridging this gap. However, accessibility and digital literacy remain critical challenges. The study emphasizes the need for policy-driven interventions that integrate community-based education, environmental health awareness, and digital health tools. Future research should explore the effectiveness of long-term digital health literacy programs and strategies for embedding environmental health education into public health policies. Strengthening interdisciplinary collaborations among healthcare professionals, educators, and policymakers is crucial to improving health literacy and reducing health disparities globally.